Taguchi optimization approach for the polypropylene fiber reinforced concrete strengthening with polymer after high temperature - Tanyildizi, Harun; Aahin, Murat (Springer, 2017)
In this study, the strengthening with polymer the polypropylene fiber reinforced concrete exposed to high temperature was examined. Taguchi L-9 (3(3)) orthogonal array was used for the design of experiments. Three different parameters were used in the study; polypropylene fiber percentage (0 %, 1 % and 2 %), high temperature degree (300 A degrees C, 600 A degrees C and 900 A degrees C) and curing period (3, 7 and 28 days). Cube samples of 100x100x100 mm sizes were produced for the compressive strength and ultrasonic pulse velocity tests. The samples were removed from the water and dried at 105 +/- 5 A degrees C, and then they were exposed to temperatures of 300 A degrees C, 600 A degrees C and 900 A degrees C. Then, the polymerization of monomer and the vinyl acetate monomer impregnation on the samples were carried out. The compressive strength and ultrasonic pulse velocity tests were made. Taguchi analysis showed that the largest compressive strength and ultrasonic pulse velocity were obtained at a rate of 0 % from the samples with polypropylene fiber exposed to 600 A degrees C and kept for 28 days as cure period. It was determined as the result of Anova analysis that high temperature had made biggest effect on the compressive strength and ultrasonic pulse velocity of the concrete reinforced with polymer.
Keywords: Concrete; Polypropylene fiber; high temperature; Polymerization; Optimization